Opportunities and challenges for sustainable business strategic planning in small and medium enterprises (MSMEs) (2018)
Approximately 90% of companies are Micro, Small, and Medium Enterprises (MSMEs) and Small & Medium Enterprises (SMEs). Their importance in the economy lies in the fact that they account for almost 60% of the jobs in the world, number which could be greater in developing countries. All these companies have an environmental impact that is almost imperceptible when observed individually, but if observed and analyzed as a whole, this impact is actually relevant. It is therefore important for these companies to include the concept of sustainability within their processes, which is difficult given the informal way they have managed their activities and processes. On the other hand, there are two paradigms that rule the concept of sustainability, weak sustainability and strong sustainability. As it will be presented in this chapter, both concepts are opposed and companies are normally oriented towards weak sustainability, because they are more interested in economic growth than in caring for the environment.